Literacies, Leadership, and Inclusive Education: Socially Just Arts-Informed Eco-Justice Pedagogy (LEARNing Landscapes, 2014)
In this article we outline the primary tasks of eco-justice education with a focus on identifying diverse cultural methods for understanding inclusion both theoretically and in educational practices. Eco-justice education involves a critical cultural and linguistic analysis of the interrelatedness of the social and ecological crises. It is through artsinformed eco-justice education practices that we are able to outline the importance of the benefits of dwelling in a learning garden. We offer specific examples of how to enact an eco-justice education curriculum in order to foster the development of eco-social inclusive habits of mind in teacher education.
Keywords: eco-justice education; literacy; leadership; arts-informed; eco-social; curriculum; teacher education